2019
DOI: 10.1111/jam.14193
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal mechanisms of α‐terpineol and terpene‐4‐alcohol as the critical components of Melaleuca alternifolia oil in the inhibition of rot disease caused by Aspergillus ochraceus in postharvest grapes

Abstract: Aims: As a natural antimicrobial agent, Melaleuca alternifolia oil (MAO) is generally recognized to be safe and effective in the inhibition of phytopathogenic fungi. Due to lack of comprehensive studies on MAO for controlling postharvest Aspergillus, we investigated the preservative mechanism of MAO and its components against Aspergillus ochraceus in postharvest grapes to evaluate their potential effectiveness as fruit preservatives. Methods and Results: In our study, the compositions in MAO were analysed by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 23 publications
2
24
0
3
Order By: Relevance
“…(-)-4-terpineol has not been reported as an antimicrobial volatile component from endophytes so far. It is similar chemically to terpene-4-alcohol (terpinen-4-ol), an isomer of (-)-4-terpineol, which has been reported as an antifungal and acts via disrupting cell walls, membranes, and cytoplasm, resulting in abnormal hyphae [30,31]. (-)-4-Terpineol may have similar antifungal mechanisms to terpene-4-alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…(-)-4-terpineol has not been reported as an antimicrobial volatile component from endophytes so far. It is similar chemically to terpene-4-alcohol (terpinen-4-ol), an isomer of (-)-4-terpineol, which has been reported as an antifungal and acts via disrupting cell walls, membranes, and cytoplasm, resulting in abnormal hyphae [30,31]. (-)-4-Terpineol may have similar antifungal mechanisms to terpene-4-alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal activity of cinnamon, oregano, peppermint and rosemary against F. oxysporum and other mico-and phytopathogens has been recently corroborated [61,62]. Regarding tea tree essential oil, several studies reported activity against a broad spectrum of phytopathogenic fungi such as Ascochyta rabiei, Colletotrichum lindemuthianum, F. graminearum, F. culmorum, Drechslera avenae, A. radicina, A. dauci and Aspergillus ochraceus [63,64], being the antifungal activity of ginger essential oil against F. oxysporum also noticeable at lower doses of only 0.3 % (v/v) [65]. On the other hand, eucalyptus, lemon eucalyptus, marjoram, scots pine and wintergreen essential oils, as well as carvacrol, showed similar antifungal activity to that of tebuconazole at 20 µL, although the fungal growth reduction was low at 10 µL and 5 µL (figure 3).…”
Section: Antimicrobial Activity Of Essential Oilsmentioning
confidence: 91%
“…As plantas, especialmente os metabólitos secundários, como os presentes nos óleos essenciais, são bem conhecidos por suas propriedades biológicas de amplo espectro (antimicrobiana, antioxidante, antitumoral, inseticida) e diversas aplicações nas indústrias farmacêutica, alimentícia e de cosméticos (ELMI et al, 2019;KONG et al, 2019;NIKOLIC et al, 2017;RAMADAN et al, 2019 KLEIN et al, 2009;LUCAS et al, 2019;SANTOS et al, 2011). Tal política estimula o avanço na comprovação científica da eficácia e da segurança das plantas medicinais e dos fitoterápicos, o aumento do número de pessoas que buscam formas alternativas de tratamento, o uso sustentável da biodiversidade e o desenvolvimento da cadeia produtiva e da indústria nacional, ampliando as opções terapêuticas e a melhoria da atenção à saúde aos usuários do SUS (BRASIL, 2009;FIGUEREDO, GURGEL e GURGEL JUNIOR, 2014;DUTRA et al, 2016;LUCAS et al, 2019;MOHAMMED, DHADED e JOSHI, 2016;OLIVEIRA et al, 2015).…”
Section: Fitoterapiaunclassified
“…Em relação aos produtos naturais, estes vêm sendo usados na medicina popular há séculos e os óleos essenciais compõem um dos grupos mais utilizados (FELIPE et al, 2018;KONG et al, 2019). Dentre eles, destaca-se o óleo essencial de Melaleuca alternifolia Cheel (Myrtaceae) (OM), também chamado de tea tree oil, o qual apresenta eficácia satisfatória no tratamento da candidíase (RASTEIRO et al, 2014;NOGUEIRA et al, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation